Aerobic Sludge Granulation in a Full-Scale Sequencing Batch Reactor. (15th April 2014) - Li, Jun; Ding, Li-Bin; Cai, Ang; Huang, Guo-Xian; Horn, Harald
Abstract : Aerobic granulation of activated sludge was successfully achieved in a full-scale sequencing batch reactor (SBR) with 50, 000 m 3  d −1 for treating a town's wastewater. After operation for 337 days, in this full-scale SBR, aerobic granules with an average SVI30 of 47.1 mL g −1, diameter of 0.5 mm, and settling velocity of 42 m h −1 were obtained. Compared to an anaerobic/oxic plug flow (A/O) reactor and an oxidation ditch (OD) being operated in this wastewater treatment plant, the sludge from full-scale SBR has more compact structure and excellent settling ability. Denaturing gradient gel electrophoresis (DGGE) analysis indicated that Flavobacterium sp., uncultured beta proteobacterium, uncultured Aquabacterium sp., and uncultured Leptothrix sp. were just dominant in SBR, whereas uncultured bacteroidetes were only found in A/O and OD. Three kinds of sludge had a high content of protein in extracellular polymeric substances (EPS). X-ray fluorescence (XRF) analysis revealed that metal ions and some inorganics from raw wastewater precipitated in sludge acted as core to enhance granulation. Raw wastewater characteristics had a positive effect on the granule formation, but the SBR mode operating with periodic feast-famine, shorter settling time, and no return sludge pump played a crucial role in aerobic sludge granulation.